OBSERVACIONES SOBRE LA BIOLOGIA DE CORINTHISCUS DENTICOLLIS (SPINOLA, 1849) (COLEOPTERA: CLERIDAE: ENOPLIINAE) Y DESCRIPCION DE LOS ESTADOS JUVENILES - Solervicens, Jaime (Acta Entomológica Chilena, 2022)
Field and laboratory observations on the biology and development of Corinthiscus denticollis (Coleóptera: Cleridae: Enopliinae) carried out at Agua Dulce (IV región, Chile) by monthly collections during May 1985 to May 1986, plus other records on the whole range of the species, are discussed in this paper. A tentative life cycle scheme is offered and observations on the copula of the species is also presented. Immature stages are also described. Association of the species with plants of genera Puya (Bromeliaceae) and Lobelia (Lobeliaceae), from xerophilous habitat in Chile, is analyzed. The potential food resources for larvae and adults is discussed. Geographical distribution of the species is established throughout records of 162 examples.